Peranan Petani Milenial mendukung Ekspor Hasil Pertanian di Indonesia - Rika Reviza Rachmawati; Endro Gunawan (Forum penelitian Agro Ekonomi, 2020)
A variety of start-ups and agricultural applications show that there has been an increasing interest in agriculture. Using information and communication technology to make agricultural products distribution and marketing more effective and efficient, millennial farmers are expected to improve the agricultural product export. However, exporting agricultural products is a challenge. Agricultural products are perishable and the exporters have to meet international food safety standards. The farmers deal with regulations, lack of facilities and infrastructures for production process, as well as the standards of Good Manufacturing Practices. This article aims to assess potentials of millennial farmers pioneering agricultural product export in Indonesia and to analyze the impact of various government policies to millennial farmers. They need appropriate technology to improve agricultural product value added and support for development potential of various agricultural start-ups. Required government supports include farm practice, export procedure training, and export market survey using internet, as well as conducive regulation easy access to financial service provider institution. Those supports will boost the millennial farmers’ spirit along with Ministry of Agriculture’s program of three-fold agricultural product export.